DOP39 Utilization and sustainability of biologics in UC - A nationwide study from the epi-IIRN. (27th May 2021) - Atia, O; Yogev, D; Friss, C; Focht, G; Orlanski-Meyer, E; Magen Rimon, R; Ledderman, N; Greenfeld, S; Kariv, R; Loewenberg Weisband, Y; Gabay, H; Nevo, D; et al.
Abstract: Background: 25% of UC patients fail to respond to induction therapy with biologics. In this nationwide study we aimed to evaluate trends in biologics utilization and sustainability in UC during the last 15 years. Methods: This study was performed on data from four the four Israeli Health Maintenance Organizations, covering 98% of the population. Sustainability was defined as continuous treatment without IBD-related surgeries and at most one short steroid course. Sustainability was compared across different biologics utilizing a propensity score (PS) weighted analysis, estimated by generalized boosted modeling (GBM). Results: 13, 231 patients were diagnosed with UC in Israel since 2005 (1, 426 [11%] pediatric-onset, 11, 805 [89%] adult-onset), of whom 1, 692 (13%) were ever treated with biologics (400 [24%] pediatric-onset, 1, 292 adults [76%], OR 3.2 [95%CI 2.8–3.6]; p<0.001) with a median of 6.4 years follow up (IQR 3.4–9.9). Infliximab was the most common first-line treatment in both children and adults (75% and 54%, respectively, p<0.001). However, in recent years there was an increase in adalimumab and vedolizumab utilization in parallel with a decrease in infliximab (Figure). The rate of initiating biologics in the first year of diagnosis increased from from 11% during 2005–2010 to 25% during 2011–2014 and 61% since 2015 (p<0.001). The use of combination therapy with immunomodulators is becoming less common and decreased with infliximab: from 36% in 2010 to 17% in 2018 (p<0.001) and with adalimumab from 32% to 12%, respectively (p<0.001). The sustainability rate in those treated with infliximab was 52% at one year from initiation of biologics, and 37% and 34% at three and five years, thereafter; compared to 55%, 43% and 40% with adalimumab and 72% and 67% after one and two years with vedolizumab. The primary non-response rate was 30% with infliximab, 31% with adalimumab and 16% with vedolizumab. Sustainability was associated with earlier initiation of biologics during the disease course (HR 0.9 [95%CI 0.85–0.95]). In the PS-adjusted model where vedolizumab served as the reference, the sustainability of both infliximab (HR 0.7 [95%CI 0.6–0.95]) and adalimumab (HR 0.8 [95%CI 0.6–0.99]) were lower. Compared with monotherapy, combination therapy increased the sustainability rate with both adalimumab (HR 0.3 [95%CI 0.2–0.6]) and infliximab (HR 0.4 [95%CI 0.-0.6]), but not with vedolizumab (HR 1.4 [95%CI 0.98–2.1]). Conclusion: Biologics are being increasingly used in UC but only half of patients sustain treatment at one year. Treatment is commenced earlier during the disease course, and this is associated with improved sustainability. Sustainability rate is higher with vedolizumab, and in combination therapy of IMM and infliximab or adalimumab.